2006
DOI: 10.1051/0004-6361:20053387
|View full text |Cite
|
Sign up to set email alerts
|

The impact of starbursts and post-starbursts on the photometric evolution of high redshift galaxies

Abstract: We present evolutionary synthesis models for galaxies of spectral types Sa through Sd with starbursts of various strengths triggered at various redshifts and study their photometric evolution before, during, and after their bursts in a cosmological context. We find that bursts at high redshift, even very strong ones, only cause a small blueing of their intrinsically blue young parent galaxies. At lower redshift, in contrast, even small bursts cause a significant blueing of their intrinsically redder galaxies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
(51 reference statements)
1
8
0
Order By: Relevance
“…Alvensleben & Fricke ; Fritze‐v. Alvensleben & Bicker ; Kotulla et al ). The recently updated BS‐SSP models (Xin et al ) considered the effects of blue straggler stars (BSs), which are likely the products of binary mergers and which seem to have a common occurrence in star clusters (see e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alvensleben & Fricke ; Fritze‐v. Alvensleben & Bicker ; Kotulla et al ). The recently updated BS‐SSP models (Xin et al ) considered the effects of blue straggler stars (BSs), which are likely the products of binary mergers and which seem to have a common occurrence in star clusters (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, stellar population synthesis has become an important and powerful tool to interpret the nature of extragalactic star clusters, including their ages, metallicities, reddening values and masses. In the past few decades, many different simple stellar population (SSP) synthesis models have been constructed and applied to study extragalactic star clusters based on photometry in multiple passbands, including Bruzual & Charlot (1993); Worthey (1994); Leitherer & Heckman (1995); Fioc & Rocca-Volmerange ⋆ E-mail: zfan@bao.ac.cn † E-mail: grijs@pku.edu.cn (1997); Maraston (1998); Vazdekis (1999); Bruzual & Charlot (2003); Yi et al (2003); Maraston (2005); Conroy et al (2009); Xin et al (2011), as well as the GALEV models (see, e.g., Schulz et al 2002Schulz et al , 2003Fritze-v. Alvensleben & Bicker 2006;Kotulla et al 2009). The recently updated BS-SSP models (Xin et al 2011) considered the effects of blue straggler stars (BSs), which are likely the products of binary mergers and which seem a common occurrence in star clusters (see, e.g., Ahumada & Lapasset 1995;Piotto et al 2002;Xin et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There have been in the past many studies devoted to the computation of integrated properties of SSPs, for example Bressan, Chiosi & Fagotto (1994), Bruzual & Charlot (2003, hereafter BC03), Leitherer et al (1999, hereafter STB99), Bicker et al (2004), González Delgado et al (2005, hereafter GON05), Maraston (2005, hereafter MAR05) and Fritze‐v. Alvensleben & Bicker (2006).…”
Section: Introductionmentioning
confidence: 99%
“…You want a red spiral? OK, but you will have to go back to z = 1-2, where Roche et al (2006) found some, along with spheroidals and mergers, among EROs (extremely red objects), an observation duly confirmed by theory (Fritze-v.Alvensleben and Bicker 2006).…”
Section: Some Special Galaxiesmentioning
confidence: 99%